Growing Greener: A Bibliometric Analysis of Green Human Resource Management - Ahmad Hafizi, Ahmad Giran; Puteri Fadzline, Muhamad Tamyez; Muhammad Ashraf, Fauzi; Nor Faradilla, Mohamed Idris (Global Academic Excellence (M) Sdn. Bhd., 2023)
A new area of study in the field of human resource management (HRM) has evolved with the increasing interest towards the environment. The objective of this paper is to investigate the geographical dispersion, magnitude and development of the knowledge foundation by pinpointing noteworthy authors, publications, and terminologies while evaluating current works and emphasizing prevalent patterns of research on green human resource management (GHRM). Using a bibliometric technique, the intellectual framework of GHRM is examined. Findings suggest four clusters in the bibliographic coupling analysis presented in environmental management (cluster 1), employee behaviour towards organizational environmental performance (cluster 2), organizational citizenship behaviour towards the environment (cluster 3), and green supply chain management (cluster 4). The implications of this study suggest that GHRM is crucial to the theoretical and managerial aspects towards sustainable development.